New Classes of Graceful Trees. (23rd November 2014) - Hossain, Md. Forhad; Aziz, Md. Momin Al; Kaykobad, M.
Abstract : Graceful labeling is one of the most researched problems. One of the earliest results is that caterpillars are graceful. We show that caterpillars connected to a vertex recursively satisfying certain conditions are also graceful.